CITRA EKSOTIK DALAM NOVEL RONGGENG DUKUH PARUK - Abu Bakar Ramadhan Muhamad (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2018)
Imaging of a discourse in the paradigm of postcolonialism is closely related to the issue of domination and subordination in terms of reference to imperialism or capitalization. The imagery is a project that develops special perceptions about